A study to determine the economic efficacy of group dental practice among U.P. Graduates in Metro Manila - de Guzman, Gary G.
In the Metro Manila area, thirty-one graduates from the U.P. College of Dentistry Classes of 1985 to 1987, currently engaged in group dental practice, responded to a questionnaire which was geared to determine the economic efficacy of this type of practice. The main areas covered are general characteristics, ownerships, investments, expenses, professional income, case load, hours spent in practice and savings. It reports primarily that the average monthly net income for dentists engaged in group practice was P 13,467 as against P 18,167 for also practitioners. The data obtained from the questionnaire proved that a group dental practice is more economically efficacious than individual practice.